Psychometric Evaluation of the Cognitive Fusion Questionnaire Among Malaysia University Students - Chua Bee Seok (Jurnal Psikologi dan Kesihatan Sosial, 2025)
The Cognitive Fusion Questionnaire (CFQ) is designed to assess individuals’ tendency to become entangled with their thoughts and the extent to which such cognitive fusion influences their behaviour. The original CFQ consists of 42 self-report items assessing daily thinking patterns and emotional experiences, although only the short version of seven items CFQ have been consistently supported by previous validation studies. The current study aimed to evaluate the psychometric properties of the short version 7-items CFQ among Malaysian university students. Using convenience sampling, a total of 343 students from five universities in Malaysia participated by completing the CFQ through Microsoft Forms and Google Forms. Results indicated acceptable internal consistency, with a Cronbach’s alpha of .70. Item analysis showed strong item–total correlations (r = .633 to r = .766). Evidence of convergent validity was demonstrated through a strong positive correlation (r = .760) with the Acceptance and Action Questionnaire–II (AAQ-II) score. Concurrent validity was supported by a significant negative correlation with the Positive Mental Health Scale (PMHS; r = –.401). Overall, the findings provide preliminary support for the reliability and validity of the CFQ in assessing cognitive fusion among Malaysian university students.